Rateb Bejalan: The Body That Remembers, The Environment, And Monotheism In The Tamiang Malay Community - Suherry, Elisa; Sunarmi, Sunarmi (Program Studi Pendidikan Sejarah - Universitas Samudra, 2026)
This article analyzes Rateb Bejalan in the Tamiang Malay community as a collective ritual that links human relations, the environment (nature), and God within the framework of Triloka/Tri Patrit aesthetics, which emphasizes this triadic relationship. This ritual is performed during the last week of the month of Safar for three consecutive nights through a procession of walking while chanting zikir from the boundary to the end of the village, with the aim of seeking divine protection, warding off danger, and praying for the protection of nature and the environment. This study uses a qualitative-interpretative approach based on literature review and analytical reading of the description of the ritual stages (deliberation, village cleansing, use of torches and tauhid flags, and closing feast). The analysis utilizes classical ritual anthropology: Durkheim to explain how collective rituals strengthen solidarity and renew collective consciousness; Turner to interpret the procession as a liminal situation that gives rise to communitas; and Geertz to read the zikir, banners, and procession as a symbolic system that shapes the religious atmosphere and drives social action. Interpretive findings show that the aesthetics of Rateb Bejalan are not merely about the beauty of form, but rather a socio-emotional mechanism that organizes the vulnerability of Safar into meaningful order, strengthens communal cohesion, and affirms the ethics of human-nature balance under the principle of monotheism.